Herramienta tecnológica interactiva para la educación en salud oral - Jácome Pacheco, Johana Stefani (2021)
The objective of this research was to analyze the influence of an interactive and educational technological tool on oral health knowledge in children aged 9-12 years, having as specific objectives: To diagnose the level of oral health knowledge of children. To design and apply an interactive technological tool based on the "Guía de educación en salud oral para promotores y estudiantes de odontología”. To identify the level of approval of the interactive technological tool based on the "Guía de educación en salud oral para promotores y estudiantes de odontología” and to evaluate the level of oral health knowledge of the children after the application of the interactive technological tool; Observational cross-sectional study with a mixed approach. The study population consisted of 118 students from the "21 de Abril" school and the "Capullitos" kindergarten, where 103 students chosen according to the selection criteria. The test and survey techniques used with the questionnaire as an instrument for both cases. The results obtained from a pre-test where it evident that children do not know about oral health, for this reason, was necessary to develop an educational software to reinforce their knowledge, which measured in a post-test where concluded that children have a low level of knowledge in oral health issues, a cutting edge technology tool designed, striking and possibly the only one of its kind, with an acceptance of 83% and approval of 99%. With the application of the tool, 81.55% of the students evaluated improved their knowledge. It recommended that the educational institutions in collaboration with universities, evaluate the levels of knowledge of each of the students about oral health, it suggested that the university teach the students of the dental career to develop technological strategies for training and evaluation.